Polymorphism of the CLDN5 gene and Schizophrenia in an Iranian Population. - Eskandar Omidinia; Fariba Mashayekhi Mazar; Parima Shahamati; Anvarsadat Kianmehr; Hamid Shahbaz Mohammadi (Tehran University of Medical Sciences, 2014)
The gene coding claudin (CLDN5) is located on 22q11. Since the proteins of CLDN5 family are a ma-jor component for barrier-forming tight junctions, it may be important to test whether or not the CLDN5 locus could be associated with schizophrenia.A total of 150 individuals affected with schizophrenia and 150 healthy persons were recruited. The relation-ship between the three single nucleotide polymorphism (SNPs) and schizophrenia disease was studied using polymer-ase chain reaction (PCR)-based restriction fragment length polymorphism (RFLP) technique. The PCR products were completely digested with restriction enzymes of DpnII, PvuII and BstNI, and then separated on agarose gel. The statis-tical investigations and haplotype analysis were also performed.The transmission disequilibrium test (TDT) exhibited weak association between rs10314 [C/G] and schizo-phrenia (v2 = 3.55, P = 0.022), but the other two SNPs did not show such an association. The global chi-square test showed that the 3-SNP haplotype system was not associated with schizophrenia although the 1-df test for individual haplotypes showed that the rs1548359(C)-rs10314(G)-rs739371(C) haplotype was excessively non-transmitted (v2 = 6.33, P = 0.025). The v2 test for LD between SNPs indicated that these three SNPs were in strong LD.Collectively, LD analysis showed that the CLDN5 locus was associated with schizophrenia in an Iranian population.